Study of the state of readiness of pharmaceutical institutions of Ukraine for implementation of integrated quality systems - S. H. Ubohov; V. V. Trokhymchuk; G. V. Zagoriy; L. O. Fedorova (The State Expert Center of the Ministry of Health of Ukraine, 2019)
One of the most promising ways to increase the efficiency of pharmaceutical enterprises in the field of quality assurance of medicines is the introduction of integrated quality systems (IQS). The aim of the work is to study of the state of readiness of pharmaceutical institutions (pharmaceutical warehouses, pharmacies) and hospital pharmaceutical services of Ukraine for the implementation of integrated quality systems. The materials of the research are: scientific publications; regulatory legal acts of the Ministry of Health of Ukraine; public reporting information of the State Service of Ukraine on Medicines and Drug Control; information posted on professional specialized websites and official websites of pharmaceutical enterprises, hospitals, health departments of local government; information obtained in the process of direct observation and questionnaire survey. Research methods are: systematic review, generalization, observation, questionnaire survey, mathematical-statistical, graphical modeling. The paper analyzes the availability of certificates of conformity to the requirements of good distribution practice (GDP) in wholesale pharmaceutical enterprises of Ukraine. The geography of the location of certified pharmaceutical warehouses in different regions of Ukraine is considered. In the context of the prospect of formation of IQS, the experience of a wholesale pharmaceutical company with respect to environmental, hygiene and safety and social responsibility is demonstrated. Based on the study of public information, the state of implementation of certified quality management systems (QMS) based on the standard ISO 9001 in pharmacies and hospitals of Ukraine is considered. The expediency of the development of the pharmaceutical IQS as an integral part of the overall QMS of the hospital is shown. Through the questionnaire survey of pharmacists, the state of readiness of Ukrainian pharmacies for the implementation of IQS based on the requirements of good practices and international standards in the field of quality, ecology, health and safety and social responsibility was explored. The state of implementation of good pharmaceutical practice (GPP), the requirements of the ISO 9001 standard, the risk management process for medicines quality, corrective and preventive actions has been studied in pharmacies. Positive tendencies and problems in the context of the readiness of pharmacies of Ukraine for the implementation of IQS have been established. Priority steps for improving the state of readiness of Ukrainian pharmacies for the implementation of IQS are identified. The research results confirm that over the last years the pharmaceutical sector of Ukraine has made significant progress towards increasing the readiness of pharmaceutical institutions for the implementation of integrated quality systems.